Corporate Capture of Development: Public-Private Partnerships, Women's Human Rights, and Global Resistance - Corina Rodríguez Enríquez; Masaya Llavaneras Blanco (Bloomsbury Academic, 2023)
Public-Private Partnerships (PPPs) have gained a renewed momentum in recent years, and have come to be viewed by governments and funders alike as a silver bullet for infrastructure development and public service provision. Critiques of the corporate capture of development are well established, yet until now the urgent question of the impacts of PPPs on women's human rights around the world has remained under-explored. This open access book aims to fill the gap, providing new insights from a set of case studies from across the Global South. Bringing an intersectional feminist approach to PPPs, these cases enable analysis that can inform advocacy and activism, whilst challenging dominant narratives and resisting the negative impacts of PPPs on women and historically marginalized communities' human rights. Widely advocating for stronger regulatory frameworks and institutions, and indicating how changes could be implemented, the examples analysed cover a range of sectors including health, energy, and infrastructure from countries including Ethiopia, Peru, India and Fiji. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Development Alternatives with Women for a New Era (DAWN).
Keywords: 320; feminism; gender; PPPs; global south; activism; human rights